Stature seekers: Cosmetic limb lengthening in medical tourism a case report - Amanda O'Halloran; Alan Walsh; Paul Harrington (JPRAS Open)
This case report details orthopaedic cosmetic surgery tourism, an emerging trend where individuals seek orthopaedic cosmetic procedures abroad. While this practice is increasingly common, it lacks regulation, potentially endangering patients. Factors driving this trend include rising healthcare costs and lengthy waitlists in public healthcare systems. Patients often pursue surgery abroad to save costs, or access specialised procedures not available domestically.However, complications can arise, necessitating costly management back home. Surgeons may face challenges due to unfamiliarity with overseas care, while patients encounter language barriers and variations in medical standards. This case report highlights a 28-year-old male who underwent bilateral limb lengthening surgery in Turkey, experiencing serious complications.While existing data on cosmetic tourism mainly focuses on plastic and bariatric surgeries, documentation specific to orthopaedic cases is limited. This report underscores the need for further research and regulation in this rapidly growing field, to ensure patient safety and optimal outcomes.